(untitled) (Acta Scientiarum. Health Sciences, 2013)
The study investigated the relationship between body image dissatisfaction, nutritional status, and eating attitudes in adolescents from a small town of the interior of São Paulo State. A total of 278 adolescents (106 boys and 172 girls) aged between 15 and 18 years had completed measures of body image dissatisfaction through the Figure Rating Scale and eating attitudes by the Eating Attitudes Test (EAT-26) and had their weight and height measured. Girls related more dissatisfaction and abnormal eating behavior than boys and, in both genders the abnormal eating attitudes tend to increase with increasing dissatisfaction. Moreover, dissatisfaction was higher between those individuals classified as overweight and obesity. These results demonstrated that body image dissatisfaction and inappropriate eating behaviors afflict boys and girls even from small cities in developing countries, highlighting the need to undertake epidemiological studies to early recognition of populations at risk of developing eating disorders.